Flame-retardant nylon material for safety shoes

CN121086516BActive Publication Date: 2026-11-03NINGBO DESHIMA IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511346150.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2026-11-03
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

现有尼龙材料在阻燃性能上不能满足需求,且添加大量阻燃剂会影响其力学性能。

Method used

The flame-retardant composite particles are designed with phytate-coated fly ash as the outer shell and ammonium polyphosphate-coated brucite as the core. A carbon protective layer is generated through physical barriers and chemical reactions, and combined with TPU nanofibers, the thermal stability and mechanical properties of nylon materials are improved.

Benefits of technology

Adding a small amount significantly improves the thermal stability and mechanical properties of nylon materials, meeting the application requirements of safety shoes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005605079910000011
    Figure BDA0005605079910000011
  • Figure BDA0005605079910000041
    Figure BDA0005605079910000041
  • Figure BDA0005605079910000051
    Figure BDA0005605079910000051
Patent Text Reader

Abstract

The application discloses a flame-retardant nylon material for safety shoes, and the flame-retardant composite particle configuration is designed in the scheme, fly ash in the form of calcium phytate coating is used as a shell, brucite in the form of ammonium polyphosphate coating is used as a core, fly ash forms a physical barrier, phosphorus elements in calcium phytate generate a char compound to promote the reaction of a carbon protective layer, and calcium phytate can generate PO free radicals in thermal degradation to slow down the release of combustible gas, brucite absorbs a large amount of heat in thermal decomposition to reduce the surface temperature, the water vapor released in decomposition can reduce the concentration of oxygen and other combustible gases, magnesium oxide produced in thermal decomposition covers the polymer surface to inhibit the contact of the polymer with oxygen and the like, heat transfer is reduced, and brucite and ammonium polyphosphate cooperate to play a role of quickly forming a carbon layer, and the composite particle in the specific configuration can greatly improve the thermal stability of the nylon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, specifically to flame-retardant nylon materials for safety shoes. Background Technology

[0002] Nylon is widely used in various industries due to its excellent comprehensive properties. To improve its mechanical properties, some companies add fillers such as fibers and inorganic particles to modify nylon, so that it has good properties such as high strength and high fatigue resistance. As a result, it is widely used in automobiles, machinery, home appliances, aviation, footwear and apparel.

[0003] The drawback is that most nylon materials on the market do not meet the requirements for flame retardant performance. Common modifications on the market include adding halogenated flame retardants or other materials such as brucite powder and fly ash to modify nylon. Taking the addition of brucite and fly ash as an example, they need to account for at least 30% to partially improve the flame retardant performance of the material. However, the large amount added affects the mechanical properties of nylon materials, which in turn affects their application. Improvements are needed. Summary of the Invention

[0004] To address at least one of the aforementioned technical deficiencies, the present invention provides the following technical solution:

[0005] This application discloses a flame-retardant nylon material for safety shoes, comprising the following components by weight:

[0006] 70-90 parts of nylon base material

[0007] 10-25 parts of flame-retardant composite particles, wherein the flame-retardant composite particles are: fly ash coated with calcium phytate as the outer shell and brucite coated with ammonium polyphosphate as the core.

[0008]

[0009] This design incorporates a flame-retardant composite particle configuration. It uses calcium phytate-coated fly ash as the outer shell and ammonium polyphosphate-coated brucite as the core. The fly ash forms a physical barrier, while the phosphorus in the calcium phytate generates phosphorus compounds to promote the formation of the char protective layer. Furthermore, calcium phytate generates PO radicals during thermal degradation, slowing the release of combustible gases. Brucite absorbs a large amount of heat during thermal decomposition, lowering the surface temperature. The released water vapor reduces the concentration of oxygen and other combustible gases. The magnesium oxide produced during thermal decomposition covers the polymer surface, inhibiting its contact with oxidants and reducing heat transfer. The combination of brucite and ammonium polyphosphate also facilitates rapid formation of an insulating char layer. Under this specific configuration, the synergistic effect of the components significantly improves the thermal stability of the nylon material. In addition, the modification of ammonium polyphosphate and calcium phytate improves the compatibility between the particles and the polymer, resulting in better mechanical properties.

[0010] TPU nanofibers in the material can reduce the material weight and improve mechanical properties.

[0011] Further, the preparation of calcium phytate-coated fly ash: fly ash particles are dispersed in water to form a turbid liquid. Ammonia water is added dropwise to the phytic acid solution to adjust the pH to neutral. The fly ash turbid liquid is added to the pH-adjusted phytic acid solution. Calcium chloride is added to the fly ash and phytic acid mixture. The mixture is stirred and reacted for 0.7-2 hours. The separated particles are washed and dried to obtain calcium phytate-coated fly ash.

[0012] Preparation of ammonium polyphosphate-coated brucite: brucite powder was mixed with ethanol to form a slurry, then polyphosphate ethanol solution was added, and after reacting for 5-20 min, dodecylamine ethanol solution was added, stirred and aged, and the separated solid reactants were washed and dried to obtain dodecylamine polyphosphate-coated brucite.

[0013] Phytate-coated fly ash and ammonium polyphosphate-coated brucite are mixed in water, the pH is adjusted to 4-6, and the mixture is reacted at 40-55℃ for 2-5 hours. After filtration to separate the reactants, washing and drying are performed to obtain flame-retardant composite particles. The molding process of flame-retardant composite particles has the advantages of being simple and easy to operate.

[0014] Furthermore, the mass ratio of calcium phytate-coated fly ash to ammonium polyphosphate-coated brucite is 2:3-6, which helps to improve the flame retardant properties of the composite particles under the limited ratio.

[0015] Furthermore, the preparation of TPU nanofibers is as follows: carbon dioxide-based TPU particles are dispersed in a mixture of DMF and acetone, ultrasonically treated, and sodium p-aminobenzenesulfonate is added. After heating, the reaction is carried out. After the reaction is completed, antioxidants and plasticizers are added to obtain TPU fiber spinning solution. The obtained spinning solution is electrospun to obtain TPU nanofibers.

[0016] Furthermore, the mass ratio of TPU particles to sodium p-aminobenzenesulfonate is 1:0.01-0.02, the volume ratio of DMF to acetone is 1:2-4, and the mass ratio of TPU particles to the mixture of DMF and acetone is 1:6-9. These specific ratios help improve the quality of TPU nanofibers.

[0017] Furthermore, the lubricant is silicone powder, the antioxidant is triphenyl phosphite, and the plasticizer is epoxidized soybean oil.

[0018] Furthermore, nylon base material, flame-retardant composite particles, TPU nanofibers, lubricant, antioxidant, and plasticizer are mixed and extruded to granulate and form nylon material.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] 1. The present invention designs the configuration and composition of flame-retardant composite particles. By adding a small amount of flame-retardant composite particles, the thermal stability of nylon materials can be greatly improved. At the same time, the addition of TPU nanofibers to this material can reduce the basis weight of nylon materials and give nylon materials better mechanical properties. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a structural diagram of modified fly ash;

[0023] Figure 2 This is a comparison of the structures of brucite before and after modification. Detailed Implementation

[0024] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0025] The TPU nanofibers used in the following preparation examples were prepared using existing technology. Specifically, carbon dioxide-based TPU particles were dispersed in a mixture of DMF and acetone and ultrasonically treated for 30 min. The volume ratio of DMF to acetone was 1:3, and the mass ratio of TPU particles to the DMF and acetone mixture was 1:8. Then, sodium p-aminobenzenesulfonate was added, with a mass ratio of TPU particles to sodium p-aminobenzenesulfonate of 1:0.01. The mixture was heated to 80℃ and reacted for 6 h, held at that temperature for 1 h, and then cooled to 50℃. Antioxidants and plasticizers were then added to obtain the TPU nanofiber spinning solution. The antioxidant was triphenyl phosphite, and the plasticizer was epoxidized soybean oil. The mass ratio of antioxidant to TPU particles was 1:100, and the mass ratio of plasticizer to TPU particles was 1:100. The resulting spinning solution was electrospun to obtain TPU nanofibers. The electrospinning parameters were as follows: current and voltage of 15 kV, spinning solution ejection rate of 0.2 ml / min, and other parameters were as per standard procedures.

[0026] In the following preparation examples, the nylon base material is nylon 6, M2400; the lubricant is silicone powder; the antioxidant is triphenyl phosphite; the plasticizer is epoxidized soybean oil; the fly ash particle size is 1.2-2.0 μm; and the brucite particle size is 5-10 μm. The brucite is pre-added to a muffle furnace and activated at 360℃ for 2 hours under nitrogen protection, then cooled to room temperature before use.

[0027] The screw extrusion granulation parameters are as follows: 190℃, 250℃, 250℃, 250℃, 250℃, 240℃, 240℃, 230℃, die head temperature is 260℃, and speed is 350r / min.

[0028] Example 1

[0029] Flame-retardant nylon material for safety shoes, by weight, comprises the following components:

[0030] 85 parts of nylon base material

[0031] 16 parts of flame-retardant composite granules;

[0032] 15 parts of TPU nanofibers

[0033] 1 part lubricant

[0034] 1 part antioxidant

[0035] 1.5 parts plasticizer.

[0036] The flame-retardant composite particles are prepared as follows:

[0037] Preparation of phytate-coated fly ash: Fly ash particles were dispersed in water to form a turbid solution (concentration 10%). Ammonia was added dropwise to adjust the pH to neutral using a phytic acid solution (concentration 56%). The fly ash turbid solution was then added to the pH-adjusted phytic acid solution (fly ash to phytic acid mass ratio 5:1). Calcium chloride was added to the fly ash and phytic acid mixture (calcium chloride to fly ash mass ratio 1:10). The mixture was stirred and reacted for 1.5 h. The mixture was filtered through a 2 μm pore size filter. The separated particles were washed and dried to obtain phytate-coated fly ash with an average particle size of 5-9 μm. Figure 1 As shown, the surface of fly ash particles is clearly covered with a rough, granular layer of calcium phytate.

[0038] Preparation of ammonium polyphosphate-coated brucite: The mass ratio of brucite powder to dodecammonium polyphosphate was 10:1. The activated brucite powder was mixed with ethanol to form a slurry (concentration 10%). Then, a corresponding amount of ethanol solution of polyphosphate (concentration 20%) was added. After reacting for 15 min, a corresponding amount of ethanol solution of dodecammonium polyphosphate (concentration 15%) was added. The mixture was stirred and aged for 10 h. The mixture was filtered through a 10 μm pore size filter. The separated solid reactants were washed and dried to obtain dodecammonium polyphosphate-coated brucite. The brucite was then ground to an average particle size of 15-25 μm. (Reference) Figure 2 , molten magnesia ( Figure 2 The left side has a clear edge, and the brucite (bluishite) is covered with dodecammonium polyphosphate. Figure 2 The right side has blurred edges and is covered with a layer of flocculent material.

[0039] Phytate-coated fly ash and ammonium polyphosphate-coated brucite were mixed in water at a mass ratio of 2:5. The pH was adjusted to 5, and the mixture was reacted at 50°C for 4 hours. The reactants were separated by filtration with a 50μm pore size, washed, dried, and ground to a particle size of 50-100μm to obtain flame-retardant composite particles.

[0040] The prepared flame-retardant composite particles are mixed with the above-mentioned components in parts by weight and then placed in a granulator for granulation.

[0041] Example 2

[0042] Flame-retardant nylon material for safety shoes, by weight, comprises the following components:

[0043]

[0044] The flame-retardant composite particles are prepared as follows:

[0045] Preparation of calcium phytate-coated fly ash: Fly ash particles were dispersed in water to form a turbid liquid (concentration 10%). Ammonia water was added dropwise to adjust the pH of the phytic acid solution (concentration 56%) to neutral. The fly ash turbid liquid was added to the pH-adjusted phytic acid solution (mass ratio of fly ash to phytic acid was 5:1). Calcium chloride was added to the fly ash and phytic acid mixture, with a mass ratio of calcium chloride to fly ash of 1:10. The mixture was stirred and reacted for 1.5 h. The mixture was filtered through a 2 μm pore size filter. The separated particles were washed and dried to obtain calcium phytate-coated fly ash with an average particle size of 5-9 μm.

[0046] Preparation of ammonium polyphosphate-coated brucite: The mass ratio of brucite powder to dodecammonium polyphosphate is 10:1. The activated brucite powder is mixed with ethanol to form a slurry (concentration 10%), and then the corresponding amount of ethanol solution of polyphosphate (concentration 20%) is added. After reacting for 15 min, the corresponding amount of ethanol solution of dodecammonium polyphosphate (concentration 15%) is added, and the mixture is stirred and aged for 10 h. The mixture is filtered through a 10 μm pore size, and the separated solid reactants are washed and dried to obtain dodecammonium polyphosphate-coated brucite, which is then ground to an average particle size of 15-25 μm.

[0047] Phytate-coated fly ash and ammonium polyphosphate-coated brucite were mixed in water at a mass ratio of 2:4.5. The pH was adjusted to 4.5, and the mixture was reacted at 50°C for 4 hours. The reactants were separated by filtration with a 50μm pore size, washed, dried, and ground to a particle size of 50-100μm to obtain flame-retardant composite particles.

[0048] The prepared flame-retardant composite particles are mixed with the above-mentioned components in parts by weight and then placed in a granulator for granulation.

[0049] Example 3

[0050] Flame-retardant nylon material for safety shoes, by weight, comprises the following components:

[0051]

[0052] The flame-retardant composite particles are prepared as follows:

[0053] Preparation of calcium phytate-coated fly ash: Fly ash particles were dispersed in water to form a turbid liquid (concentration 10%). Ammonia water was added dropwise to adjust the pH of the phytic acid solution (concentration 56%) to neutral. The fly ash turbid liquid was added to the pH-adjusted phytic acid solution (mass ratio of fly ash to phytic acid was 5:1). Calcium chloride was added to the fly ash and phytic acid mixture, with a mass ratio of calcium chloride to fly ash of 1:10. The mixture was stirred and reacted for 1.5 h. The mixture was filtered through a 2 μm pore size filter. The separated particles were washed and dried to obtain calcium phytate-coated fly ash with an average particle size of 5-9 μm.

[0054] Preparation of ammonium polyphosphate-coated brucite: The mass ratio of brucite powder to dodecammonium polyphosphate is 10:1. The activated brucite powder is mixed with ethanol to form a slurry (concentration 10%), and then the corresponding amount of ethanol solution of polyphosphate (concentration 20%) is added. After reacting for 15 min, the corresponding amount of ethanol solution of dodecammonium polyphosphate (concentration 15%) is added, and the mixture is stirred and aged for 10 h. The mixture is filtered through a 10 μm pore size, and the separated solid reactants are washed and dried to obtain dodecammonium polyphosphate-coated brucite, which is then ground to an average particle size of 15-25 μm.

[0055] Phytate-coated fly ash and ammonium polyphosphate-coated brucite were mixed in water at a mass ratio of 1:3. The pH was adjusted to 5, and the mixture was reacted at 50°C for 4 hours. The reactants were separated by filtration with a 50μm pore size, washed, dried, and ground to an average particle size of 50-100μm to obtain flame-retardant composite particles.

[0056] The prepared flame-retardant composite particles are mixed with the above-mentioned components in parts by weight and then placed in a granulator for granulation.

[0057] Comparative Example 1

[0058] Compared with Example 1, the difference is that: in this example, there is no calcium phytate coating process and no dodecylamine polyphosphate coating process. The dodecylamine polyphosphate, calcium phytate, fly ash and brucite are physically mixed and then added for granulation.

[0059] Comparative Example 2

[0060] Compared with Example 1, the difference is that: in this example, there is no calcium phytate coating process, and calcium phytate, fly ash and dodecylamine polyphosphate-coated magnesia are physically mixed and then added for granulation.

[0061] The performance of the nylon materials molded in the above embodiments and comparative examples was tested, and the results are shown in Table 1:

[0062] Table 1

[0063] Limiting oxygen index / % Flame retardant rating (UL94) Example 1 32 V-0 Example 2 33 V-0 Example 3 32 V-0 Comparative Example 1 23 V-1 Comparative Example 2 25 V-1 Nylon 6 21.0 /

[0064] As can be seen from the table above, the addition of flame-retardant composite particles with specific configurations significantly improves the flame-retardant performance of the molded nylon material. Furthermore, the nylon material molded according to test examples 1-3 has a tensile strength of over 69 MPa and a flexural strength of over 108 MPa, exhibiting good mechanical properties that meet the application requirements in the footwear field.

[0065] The above are merely preferred embodiments of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principle of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A flame-retardant nylon material for safety shoes, characterized in that, By mass, it includes the following components: 70-90 parts of nylon base material 10-25 parts of flame-retardant composite particles, wherein the flame-retardant composite particles are: fly ash coated with calcium phytate as the outer shell and brucite coated with dodecylamine polyphosphate as the core. 10-15 parts of TPU nanofibers 0.5-1.5 parts lubricant Antioxidant 0.5-1.5 parts 1-3 parts plasticizer; Preparation of calcium phytate coated fly ash: Fly ash particles are dispersed in water to form a turbid liquid. Ammonia water is added dropwise to the phytic acid solution to adjust the pH to neutral. The fly ash turbid liquid is added to the pH-adjusted phytic acid solution to form a mixed liquid. Calcium chloride is added to the mixed liquid and stirred for 0.7-2 hours. The separated particles are washed and dried to obtain calcium phytate coated fly ash. Preparation of dodecylamine polyphosphate-coated brucite: brucite powder was mixed with ethanol to form a slurry, then polyphosphate ethanol solution was added, and after reacting for 5-20 min, dodecylamine ethanol solution was added, and the mixture was stirred and aged. The separated solid reactants were washed and dried to obtain dodecylamine polyphosphate-coated brucite. Calcium phytate-coated fly ash and dodecylamine polyphosphate-coated brucite are mixed in water, the pH is adjusted to 4-6, and the reaction is carried out at 40-55℃ for 2-5 hours. The reactants are separated by filtration, washed and dried to obtain flame-retardant composite particles. The mass ratio of calcium phytate-coated fly ash to dodecylamine polyphosphate-coated brucite is 2:3-6.

2. The flame-retardant nylon material for safety shoes as described in claim 1, characterized in that: The preparation of TPU nanofibers is as follows: carbon dioxide-based TPU particles are dispersed in a mixture of DMF and acetone, ultrasonically treated, and sodium p-aminobenzenesulfonate is added. After heating, the reaction is carried out. After the reaction is completed, antioxidants and plasticizers are added to obtain TPU fiber spinning solution. The obtained spinning solution is electrospun to obtain TPU nanofibers.

3. The flame-retardant nylon material for safety shoes as described in claim 2, characterized in that: The mass ratio of TPU particles to sodium p-aminobenzenesulfonate is 1:0.01-0.02, the volume ratio of DMF to acetone is 1:2-4, and the mass ratio of TPU particles to the mixture of DMF and acetone is 1:6-9.

4. The flame-retardant nylon material for safety shoes as described in claim 2, characterized in that: The lubricant is silicone powder, the antioxidant is triphenyl phosphite, and the plasticizer is epoxidized soybean oil.

5. The flame-retardant nylon material for safety shoes as described in claim 1, characterized in that: Nylon base material, flame-retardant composite particles, TPU nanofibers, lubricant, antioxidant, and plasticizer are mixed and extruded to form nylon material.

Citation Information

Patent Citations

  • Microencapsulated ammonium polyphosphate modified PA6 material, preparation method thereof and high-voltage connector

    CN115197566A

  • Ammonium polyphosphate microcapsule and method for preparing low-smoke halogen-free flame-retardant PA6 by using same

    CN118791779A